Determining the relationship between the quadriceps and tibiofemoral angles among adolescents - Maha H. El Gharib, MD; Amira M. El Tohamy, PhD; Nanees E. Mohamed, PhD (Journal of Taibah University Medical Sciences, 2021)
الملخص: أهداف البحث: فحص وجود أو عدم وجود علاقة بين زاوية العضلة الرباعية وزاوية الساق والفخذ، والمقارنة بين الطرفين السفليين فيما يتعلق بالطرف المهيمن، وفحص وجود اختلاف من عدمه في حالة ممارسة الرياضة. طرق البحث: شارك في البحث ١٥٠ من اليافعين من عمر ١٢-١٨، وتم تقسيمهم إلي مجموعتين. مجموعة أ (المجموعة الرياضية)، بما في ذلك أربع مجموعات فرعية من مختلف الرياضات، ومجموعة ب (المجموعة غير الرياضية)، وتم قياس الزوايا عن طريق التصوير المحوسب. النتائج: وجدت علاقة قوية بين زاوية العضلة الرباعية وزاوية الساق والفخذ، ووجد اختلاف بين الطرفيين السفليين فيما يتعلق بقيم نفس الزوايا، ووجد اختلاف في القيم لنفس الزوايا بين الممارسين للرياضة وغير الممارسين للرياضة. ولكن لا يوجد اختلاف بين الرياضات المختلفة. الاستنتاجات: لابد من قياس الزوايتين عند التقييم، والفحص للطرف السفلي مع مراعاة قياس كل طرف على حدا، وأيضا لابد من الأخذ في الاعتبار ممارسة الشخص للرياضة من عدمه عند التقييم. Abstract: Objectives: This study aims to determine the relationship between the quadriceps angle (Q-angle) and tibiofemoral angle (TF-angle) among adolescents. We also compared the angles between both the lower limbs with respect to dominancy, measured the difference between athletic and non-athletic angles, and explored the variations of these features in different sports. Methods: We recruited 150 adolescents aged between 12 and 18 years and classified them into two groups; group A (athletic group), including four subgroups of players of different sports, and group B (non-athletic group). We measured the Q-angle and TF-angle via computerized photogrammetry. Results: This study showed a strong and statistically significant relationship between Q-angle and TF-angle (p < 0.05). Similarly, we found a statistically significant difference in the Q-angle and TF-angle between both the lower limbs concerning dominance. Lastly, we identified a significant difference between the athletic and non-athletic groups. However, there was no difference among players of different sports (p > 0.05). Conclusion: Our study showed a strong relationship between the Q-angle and the TF-angle. The Q-angle and the TF-angle should be measured bilaterally and the nature of sports should also be considered.